The CARM1 transcriptome and arginine methylproteome mediate skeletal muscle integrative biology - Tiffany L. vanLieshout; Derek W. Stouth; Nicolas G. Hartel; Goutham Vasam; Sean Y. Ng; Erin K. Webb; Irena A. Rebalka; Andrew I. Mikhail; Nicholas A. Graham; Keir J. Menzies; Thomas J. Hawke; Vladimir Ljubicic (Elsevier, 2022)
Objective: Coactivator-associated arginine methyltransferase 1 (CARM1) catalyzes the methylation of arginine residues on target proteins to regulate critical processes in health and disease. A mechanistic understanding of the role(s) of CARM1 in skeletal muscle biology is only gradually emerging. The purpose of this study was to elucidate the function of CARM1 in regulating the maintenance and plasticity of skeletal muscle. Methods: We used transcriptomic, methylproteomic, molecular, functional, and integrative physiological approaches to determine the specific impact of CARM1 in muscle homeostasis. Results: Our data defines the occurrence of arginine methylation in skeletal muscle and demonstrates that this mark occurs on par with phosphorylation and ubiquitination. CARM1 skeletal muscle-specific knockout (mKO) mice displayed altered transcriptomic and arginine methylproteomic signatures with molecular and functional outcomes confirming remodeled skeletal muscle contractile and neuromuscular junction characteristics, which presaged decreased exercise tolerance. Moreover, CARM1 regulates AMPK-PGC-1α signalling during acute conditions of activity-induced muscle plasticity. Conclusions: This study uncovers the broad impact of CARM1 in the maintenance and remodelling of skeletal muscle biology.